Waterbeheer en ideologische belangen in de premoderne Nederlanden - Van der Meulen, Jim (TSEG - The Low Countries Journal of Social and Economic History, 2023)
This article argues that the long-term development of premodern Dutch water management was partly shaped through a combination of institutional factors, and cultural norms and values. Departing from the institutional focus in the narrow sense that predominates in Milja van Tielhof’s Consensus and conflict, it makes the case that historians should take into account the influence of changes in the nature and ideology of the Dutch political elite between the late medieval ‘princely period’ and the early modern Dutch Republic. This is mainly demonstrated in reference to changes around the ideological precept of the Common Good (bonum commune). Using a combination of late medieval and early modern examples, the central contention is that the oligarchical elite that came to dominate both water management and the overarching political structure of the Dutch Republic, acquired a new notion of ‘shared interests’ due to their engagement on all political levels of the new state.